Trafficking in diamonds - Siegel, Dina (Henry Stewart Talks, 2009)
Historical development of the diamond business, Diamond pipeline, The criminal acquisition of diamonds, Production countries, Processing centers, Transit and wholesale, Trafficking in 'conflict diamonds', Diamonds and organized crime, What can be done?
Archived at 2022/04/03